A Concept Analysis on Culturally Congruent Care - Salinda, Ma. Theresa; Hipona, Jocelyn Baluyot; Ilarde, Marivic; Tuazon, Alicia (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Culturally Congruent is providing quality care that promote cultural competency. This include extreme humility and extreme openness and acceptance of different culture in beliefs, values, and discipline.Purpose: This study aims to provide quality patient care despite the challenges in the healthcare plans like misinformation, mistrust and misinterpretation. The nurse should provide quality health care that suit to patient culture.Methods: The method use is a case analysis. The eight steps of this method are: 1) Selecting a concept; 2) Determining the aims or purposes of analysis; 3) Identifying all uses of the concept; 4) Determining the defining attributes of the concept; 5) Constructing a model case; 6) Constructing borderline, contrary, invented, and illegitimate cases;Â 7) Identifying antecedents and consequences; and 8) Defining empirical references.Results: The theory of culture care emphasizes in the uniqueness of nursing as a means to know and help the culture in the field of clinical practice. Culturally based care factors are recognized as major influence upon human expressions related to health and illness. The theory also serves as guide to nursesâ€™ thinking, practice and in research development.Conclusion: Integrating cultural competence models will promote effectiveness in nursing practice.